Pengaruh Promosi terhadap Minat Beli Konsumen Dapur Atha Kecamatan Panyabungan Kabupaten Mandailing Natal - Fitriani Fitriani; Vebri Sugiharto; Ade Khadijatul Z. Hrp (Jurnal Inovasi Ekonomi Syariah dan Akuntansi, 2024)
The purpose of this research is to determine the influence of advertising on consumer purchasing intentions in the Kitchen Equipment business and to determine the extent of the influence of advertising on consumer products. The research method used is a quantitative method with descriptive data using stratified sampling. The sample for this research consisted of 100 people and the measurement method used SPSS version 21 software. Data analysis used the t test, obtained tcount of 20.805 and ttable of 1.664 at a significance level of 5%, so that tcount > ttable was obtained. This shows that advertising influences consumers' purchasing intentions in Dapur Ata, Panybungan District, Mandailing Natal Regency.